2004
DOI: 10.1111/j.1467-2494.2004.00238.x
|View full text |Cite
|
Sign up to set email alerts
|

Advances in sebaceous gland research: potential new approaches to acne management

Abstract: Sebaceous gland development and function is regulated by an expanding array of molecules including transcription factors, hormones, retinoids, growth factors, cytokines and nuclear hormone receptors. We have reviewed the literature to present the current understanding of sebaceous gland development and physiology, with particular emphasis on the control of the sebaceous gland and its implications for acne management. Interestingly, retinoids, cytokines and nuclear hormone receptors appear to be promising inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 186 publications
(203 reference statements)
1
20
0
Order By: Relevance
“…It is accepted that to synthesize lipids, sebaceous glands need energy that may be acquired through the betaoxidation of fatty acids and/or glucose catabolism. 35 According to Downine and Kaealey, the pattern of lipid synthesis is maintained by the endogenous glycogen, an important NADPH supplier, for the synthesis of triglycerides. Therefore, it is possible that the ingestion of food with a low glycemic index may alter the stock of glycogen in sebaceous glands, and this may be a limiting factor in sebaceous lipogenesis.…”
Section: Hypothesis N 0 6: Corroborating Evidence Of the Association mentioning
confidence: 99%
See 2 more Smart Citations
“…It is accepted that to synthesize lipids, sebaceous glands need energy that may be acquired through the betaoxidation of fatty acids and/or glucose catabolism. 35 According to Downine and Kaealey, the pattern of lipid synthesis is maintained by the endogenous glycogen, an important NADPH supplier, for the synthesis of triglycerides. Therefore, it is possible that the ingestion of food with a low glycemic index may alter the stock of glycogen in sebaceous glands, and this may be a limiting factor in sebaceous lipogenesis.…”
Section: Hypothesis N 0 6: Corroborating Evidence Of the Association mentioning
confidence: 99%
“…Therefore, it is possible that the ingestion of food with a low glycemic index may alter the stock of glycogen in sebaceous glands, and this may be a limiting factor in sebaceous lipogenesis. 35,36 It is suggested that food with a low glycemic index influences sebum composition by means of metabolic effects and/or, secondarily, levels of free testosterone and androgens. Evidence shows that a low glycemic index diet can lower glycogen stocks in the tissues of the body (muscle and liver), thus limiting sebaceous lipogenesis.…”
Section: Hypothesis N 0 6: Corroborating Evidence Of the Association mentioning
confidence: 99%
See 1 more Smart Citation
“…Production of sebum depends on the density, location and activity of sebaceous glands [25]. In such areas as the scalp, the T zone of the face, the sternum or the interscapular areas, their density amounts to 900 per square centimetre of the skin, but in other places less than 100 sebaceous glands per square centimetre are observed [19,26].…”
mentioning
confidence: 99%
“…58 The ductal epithelium, which comprises three layers (basal, intermediate, granular layers), lies between these quiescent stem cells and the transit-amplifying "basal" cells that encapsulate the distal part of the SG. 57 Whether the various cell types in the ductal epithelium and gland per se represent different steps along a single path to differentiation, or are the product of distinct differentiation programs from a common progenitor, is unknown, as is the pattern of cell movement within SG.…”
Section: Discussionmentioning
confidence: 99%